2014
DOI: 10.1371/journal.pone.0098544
|View full text |Cite|
|
Sign up to set email alerts
|

BRMS1 Suppresses Glioma Progression by Regulating Invasion, Migration and Adhesion of Glioma Cells

Abstract: Breast cancer metastasis suppressor 1 (BRMS1) is a metastasis suppressor gene in several solid tumors. However, the expression and function of BRMS1 in glioma have not been reported. In this study, we investigated whether BRMS1 play a role in glioma pathogenesis. Using the tissue microarray technology, we found that BRMS1 expression is significantly decreased in glioma compared with tumor adjacent normal brain tissue (P<0.01, χ2 test) and reduced BRMS1 staining is associated with WHO stages (P<0.05, χ2 test). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 38 publications
5
20
0
Order By: Relevance
“…In addition, the overexpression of p40 significantly inhibits human cell growth [29]. In this study, the expression value of BRMS1L was down-regulated, which is consistent with the previous studies about BRMS1 and p40 [27,29]. These findings indicated that BRMS1L might play a GAPN glioma associated protein-protein interaction network Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, the overexpression of p40 significantly inhibits human cell growth [29]. In this study, the expression value of BRMS1L was down-regulated, which is consistent with the previous studies about BRMS1 and p40 [27,29]. These findings indicated that BRMS1L might play a GAPN glioma associated protein-protein interaction network Fig.…”
Section: Discussionsupporting
confidence: 91%
“…However, BRMS1L codes a family of breast cancer metastasis suppressor 1-like (BRMS1L) proteins. Breast cancer metastasis suppressor 1 (BRMS1) is a member of the mSin3-HDAC transcription corepressor complex [26], and is significantly down-regulated in glioma compared with adjacent non-tumor tissue [27]. The overexpression of BRMS1 inhibits glioma cell invasion, migration, and adhesion capacity by suppressing NF-κB, uPA, MMP-2, and Src-FAK pathway [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BRMS1 also regulates a network of proteins with central roles in cancer metastasis (19,34). For instance, Mei et al (35) demonstrated that BRMS1 was able to inhibit the invasion of glioma cells by suppressing urokinase-type plasminogen activator, nuclear factor-κB and the expression and enzymatic activity of matrix metalloproteinase-2 (MMP-2). You et al (36) reported that BRMS1 is able to regulate apoptosis in NSCLC cells by modulating the activation of signal transducer and activator of transcription 3.…”
Section: Discussionmentioning
confidence: 99%
“…64 Motility was quantified as the percentage of the initial wound distance covered by the cells after 24 h. Consistent with previous studies, expression of wild-type BRMS1 significantly reduced the ability of MDA-MB-231 cells to migrate. [65][66][67] Therefore, while vector control MDA-MB-231 cells covered 81.3 % of the wound area within 24 hours, MDA-MB-231 cells expressing wild-type BRMS1 only covered 57.7% of the wound area ( Fig. 3A).…”
Section: Phosphorylation Of Brms1 On Serine 237 Affects Cell Migrationmentioning
confidence: 97%